PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN PEMAHAMAN KONSEP SISWA SMP PADA MATERI OPTIK - Hasugian, Julkifri Hasugian; Murni; Franky A.M. Lumbantobing (Prosiding Seminar Nasional Pendidikan IPA, 2025)
The success of learning carried out in the classroom depends on and is greatly influenced by the abilities of each student. Low student abilities such as problem solving and conceptual understanding are two things that need to be considered during learning in the classroom. Therefore, the solution offered to improve problem solving and conceptual understanding is to use the PBL model. The objectives of this study are (a) to improve problem solving skills, (b) to improve conceptual understanding skills, (c) to obtain differences in the increase in problem solving skills between the experimental class and the control class, and (d) to obtain differences in the increase in conceptual understanding skills between the experimental class and the control class. This research method is a quasi-experimental type with a Nonequivalent Control Group Design. The samples used in this study were class VIII-1 and class VIII-3 at one of the State Junior High Schools in Tangerang in the even semester of the 2023/2024 academic year. The instruments used were multiple choice questions and essays. Based on the results of the research data analysis, it was found that the implementation of PBL on optics material showed that: (a) the PBL model can improve problem-solving skills, (b) the PBL model can improve conceptual understanding skills, (c) there is a difference in the improvement of problem-solving skills between the experimental class and the control class, and (d) there is a difference in the improvement of conceptual understanding skills between the experimental class and the control class.